The influence of ERP simulation on enterprise system learning outcome - Primanita Setyono; Heidar Arnandiansyah (Jurnal Akuntansi dan Auditing Indonesia, 2018)
This study aims to examine how Enterprise Resurce Planning simulation (ERPsim) enhance the outcome of learning Enterprise Systems Course for accounting students. The sample of this study is undergraduate accounting students who have taken an Enterprise System course and ERPsim. The sample used in this study is 140 respondents selected using purposive sampling, The data analysis is conducted through Structural Equation Modelling (SEM). The result of this research indicates that two factors determining the behavior for learning Enterprise systems course are enjoyment and cognitive appraisal. The result of this study provides evidence that behavior intention to use ERPsim is related positively to learning outcomes. Enjoyment is related positively to cognitive appraisal for using ERPsim. Enjoyment and cognitive appraisal have an important role in the effectiveness of using ERPsim in understanding business processes and enterprise system.